Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai (Studi pada Pegawai di Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Pesisir Selatan) - Adilah Rahmah; Dista Sakila; Natasha Amanda; Regil Aurel; Syaibullah Saf’i; Syamsir Syamsir (Jurnal Ilmu Hukum, Humaniora dan Politik, 2023)
Leaders are very important in an organization because leaders are agents of change. A leader must pay attention to his leadership style when carrying out his duties as a leader. If the employee's leadership style is good, the employee's performance will be good and will increase, and vice versa, if the employee's leadership style is not good, the employee's performance will be bad or even decrease. This research is a quantitative descriptive analysis that tries to show the influence of leadership style on employee performance. The instrument used in this research is a questionnaire, while the variables used in this research are the independent variable, namely leadership style (X) and the dependent variable is employee performance (Y). The research results show a strong relationship between leadership style and employee performance, based on the determination calculations studied, it produces a value of 86.4% which shows that the influence of leadership style on employee performance and the remaining 13.6% is influenced by other factors.